Priority areas for large mammal conservation in Equatorial Guinea. - Mizuki Murai (PLoS ONE, 2013)
Hunting is one of the main driving forces behind large mammal density distribution in many regions of the world. In tropical Africa, urban demand for bushmeat has been shown to dominate over subsistence hunting and its impact often overrides spatial-ecological species characteristics. To effectively protect remaining mammal populations the main factors that influence their distribution need to be integrated into conservation area prioritisation and management plans. This information has been lacking for Río Muni, Equatorial Guinea, as prior studies have been outdated or have not systematically covered the continental region of the country. In this study we evaluated: 1) the relative importance of local vs. commercial hunting; 2) wildlife density of protected vs. non-protected areas; and 3) the importance of ecological factors vs. human influence in driving mammal density distribution in Río Muni. We adopted a systematic countrywide line transect approach with particular focus on apes and elephants, but also including other mammal species. For analysis of field data we used generalised linear models with a set of predictor variables representing ecological conditions, anthropogenic pressure and protected areas. We estimate that there are currently 884 (437-1,789) elephants and 11,097 (8,719-13,592) chimpanzees and gorillas remaining in Río Muni. The results indicate strong hunting pressures on both local and commercial levels, with roads demonstrating a negative impact on elephants and overall mammal body mass. Protected areas played no role in determining any of the mammal species distributions and significant human hunting signs were found inside these protected areas, illustrating the lack of environmental law enforcement throughout the country. Río Muni is currently under-represented in conservation efforts in Western Equatorial Africa, and we recommend a focus on cross-boundary conservation, in particular in the Monte Alén-Monts de Cristal and Río Campo Ma'an conservation landscapes, where the highest densities and diversity of large mammals remain.